2021
DOI: 10.1038/s41577-021-00626-8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons in self-defence: inhibition of virus entry by intrinsic immunity

Abstract: Virus entry, consisting of attachment to and penetration into the host target cell, is the first step of the virus life cycle and is a critical ‘do or die’ event that governs virus emergence in host populations. Most antiviral vaccines induce neutralizing antibodies that prevent virus entry into cells. However, while the prevention of virus invasion by humoral immunity is well appreciated, considerably less is known about the immune defences present within cells (known as intrinsic immunity) that interfere wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 158 publications
0
57
0
2
Order By: Relevance
“…Rapamycin, everolimus, and especially temsirolimus boosted HA- and VSV G-mediated infections (up to 30-fold and 11-fold, respectively) (Figure 4D-E) . Since IFITM proteins have been previously shown to inhibit infection by SARS-CoV-1, MERS-CoV, VSV, and Influenza A virus [40], these data suggest that rapalogs promote infection, at least in part, by lowering the barrier to virus entry imposed by IFITM proteins.…”
Section: Resultsmentioning
confidence: 93%
“…Rapamycin, everolimus, and especially temsirolimus boosted HA- and VSV G-mediated infections (up to 30-fold and 11-fold, respectively) (Figure 4D-E) . Since IFITM proteins have been previously shown to inhibit infection by SARS-CoV-1, MERS-CoV, VSV, and Influenza A virus [40], these data suggest that rapalogs promote infection, at least in part, by lowering the barrier to virus entry imposed by IFITM proteins.…”
Section: Resultsmentioning
confidence: 93%
“…An important part of the innate antiviral immunity is represented by the intrinsic immunity, which is mediated by constitutively expressed or induced factors that recognize specific viral components and restrict the viral multiplication cycle, rendering host cells non-permissive to a certain virus [40]. These proteins could be included in the PRR category, as they bind directly to viral components; however, unlike other PRRs that inhibit viral infection indirectly by inducing interferons and other antiviral molecules, intrinsic antiviral factors block the viral replication immediately and directly, often before the onset of the IFN response [41].…”
Section: Antiviral Immune Response In Sars-cov-2 Infectionmentioning
confidence: 99%
“…This work focuses on chol. A body of literature has demonstrated that chol chemistry and concentration dramatically affect virus-endosome fusion [17, 32], as well as plasma membrane fusion and fission [16, 33]. Understanding chol’s role in mechanics is complicated by disparate observations.…”
Section: Introductionmentioning
confidence: 99%